Pengaruh Diferensiasi Produk Terhadap Kepuasan Konsumen - Bintang Balele; Muhtazib Muhtazib (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the effect of product differentiation on consumer satisfaction at the Alfamart Mini Market, Rappocini Branch, Makassar City. The research method used is quantitative research methods. 1. Results of simple linear regression analysis in the form of the equation Y = 14.612 + 0.672 sales services will increase. The correlation coefficient r = 0.747 or r = 74.7% shows a positive relationship between variable X (Product Differentiation) and Variable Y (Consumer Satisfaction). The results of hypothesis testing with a significance level of 5% (0.05), obtained tcount = 30.55 > ttable = 2.048. This illustrates that the hypothesis put forward regarding product differentiation has an effect on consumer satisfaction at the Alfamart Mini Market, Rappocini Makassar Branch, is accepted.